2022
DOI: 10.3390/nu14194117
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease and Customized Nutritional Intervention Focusing on Gut Microbiome Balance

Abstract: Inflammatory bowel disease (IBD) represents a chronic relapsing–remitting condition affecting the gastrointestinal system. The specific triggering IBD elements remain unknown: genetic variability, environmental factors, and alterations in the host immune system seem to be involved. An unbalanced diet and subsequent gut dysbiosis are risk factors, too. This review focuses on the description of the impact of pro- and anti-inflammatory food components on IBD, the role of different selected regimes (such as Crohn’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 154 publications
(173 reference statements)
0
4
0
Order By: Relevance
“…The reluctance to consume fruit, vegetables and legumes observed in patients with IBD, caused by the fear of symptom exacerbation and the hope of sustaining remission, contributes to nutritional deficiencies, as shown in studies [64][65][66][67]. This undoubtedly has an impact on the shift away from the Mediterranean pattern observed over the past decade or so, even in the Mediterranean populations.…”
Section: Discussionmentioning
confidence: 99%
“…The reluctance to consume fruit, vegetables and legumes observed in patients with IBD, caused by the fear of symptom exacerbation and the hope of sustaining remission, contributes to nutritional deficiencies, as shown in studies [64][65][66][67]. This undoubtedly has an impact on the shift away from the Mediterranean pattern observed over the past decade or so, even in the Mediterranean populations.…”
Section: Discussionmentioning
confidence: 99%
“…It is vital to note that the prohealthy diet index was higher among healthy subjects than the CD and UC groups. It is reasonable to assume that products associated with a higher prohealthy index – such as wholemeal bread, milk, legumes, fruits and vegetables – are usually avoided by IBD patients because their large consumption may worsen the gastrointestinal symptoms 32 . Moreover, Dolovich et al reported that a moderate health diet score was weakly associated with active inflammation; however, moderate health diet score was linked to symptoms of IBD.…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to assume that products associated with a higher prohealthy indexsuch as wholemeal bread, milk, legumes, fruits and vegetablesare usually avoided by IBD patients because their large consumption may worsen the gastrointestinal symptoms. 32 Moreover, Dolovich et al reported that a moderate health diet score was weakly associated with active inflammation; however, moderate health diet score was linked to symptoms of IBD. Authors suggested it was caused by the intake of fruits and vegetables, which may influence the gastrointestinal tract of IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Crohn’s disease (CD), one of the main phenotypes of inflammatory bowel disease (IBD), can affect any part of the gastrointestinal tract ( Fiorindi et al, 2022 ; Godala et al, 2022 ). It can impact the function of gastrointestinal secretions, as well as increasing the intestinal permeability leading to an aberrant immunological response and subsequent intestinal inflammation ( Chichlowski and Hale, 2008 ).…”
Section: Introductionmentioning
confidence: 99%